Small interfering RNA delivery by polyethylenimine-functionalised porous silicon nanoparticles. (7th September 2015) - Hasanzadeh Kafshgari, M.; Alnakhli, M.; Delalat, B.; Apostolou, S.; Harding, F. J.; Mäkilä, E.; Salonen, J. J.; Kuss, B. J.; Voelcker, N. H.
Abstract : Polyethyleneimine-coated mesoporous silicon nanoparticles efficiently deliver siRNA in glioblastoma cells, subsequently reducing the protein expression of a chemotherapy resistance gene by 70% within 72 hours. Abstract : In this study, thermally hydrocarbonised porous silicon nanoparticles (THCpSiNPs) capped with polyethylenimine (PEI) were fabricated, and their potential for small interfering RNA (siRNA) delivery was investigated in an in vitro glioblastoma model. PEI coating following siRNA loading enhanced the sustained release of siRNA, and suppressed burst release effects. The positively-charged surface improved the internalisation of the nanoparticles across the cell membrane. THCpSiNP-mediated siRNA delivery reduced mRNA expression of the MRP1 gene, linked to the resistence of glioblastoma to chemotherapy, by 63% and reduced MRP1-protein levels by 70%. MRP1 siRNA loaded nanoparticles did not induce cytotoxicity in glioblastoma cells, but markedly reduced cell proliferation. In summary, the results demonstrated that non-cytotoxic cationic THCpSiNPs are promising vehicles for therapeutic siRNA delivery.